2007
DOI: 10.1111/j.1742-7843.2007.00126.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Reactivating and Therapeutic Efficacy of Two Salts of the Oxime HI‐6 against Tabun, Soman and Cyclosarin in Rats

Abstract: Abstract:The reactivating and therapeutic efficacy of two salts of the oxime HI-6 (dichloride and dimethanesulphonate) against chosen nerve agents (tabun, soman and cyclosarin) was compared in rats. The potency of both salts of HI-6 to decrease the acute toxicity of tabun, soman and cyclosarin was similar in nerve agent-poisoned rats. While the potency of HI-6 dichloride and HI-6 dimethanesulphonate to counteract acute toxic effects of tabun is rather low, both salts of HI-6 were able to decrease the acute tox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…In atropine (10)-pretreated rats, HI-6 (15) raised the LD 50 of soman (3) 5.7 times and additional intracerebroventricular injections of HI-6 (15) failed to enhance this protection further [101]. This may, however, not come as a surprise, because HI-6 (15) is unable to reactivate soman (3)-inhibited brain acetylcholinesterase [102][103][104]. Sarin (2) induced hypothermia, which is considered to be the result of muscarinic receptor stimulation in the hypothalamus, can be effectively antagonized by HI-6 (15) [108].…”
Section: Brain Entry Of Oximesmentioning
confidence: 70%
See 1 more Smart Citation
“…In atropine (10)-pretreated rats, HI-6 (15) raised the LD 50 of soman (3) 5.7 times and additional intracerebroventricular injections of HI-6 (15) failed to enhance this protection further [101]. This may, however, not come as a surprise, because HI-6 (15) is unable to reactivate soman (3)-inhibited brain acetylcholinesterase [102][103][104]. Sarin (2) induced hypothermia, which is considered to be the result of muscarinic receptor stimulation in the hypothalamus, can be effectively antagonized by HI-6 (15) [108].…”
Section: Brain Entry Of Oximesmentioning
confidence: 70%
“…Pralidoxime (11) was found to be unable to reactivate brain acetylcholinesterase after sarin (2) intoxication [100], whereas HI-6 (15) only reactivated acetylcholinesterase in the central nervous system after inhibition by sarin (2), but not by soman (3) or tabun (1) [4,[101][102][103][104]. On the other hand, one of the newly developed oximes (K-74 (18)) was shown to be an efficacious reactivator of tabun-inhibited acetylcholinesterase in the brain [103].…”
Section: Brain Entry Of Oximesmentioning
confidence: 97%
“…Thus, bis-pyridinium reactivators can occupy both sites (peripheral aromatic site and catalytic anionic site) and confer the compounds inhibitory ability towards AChE as confirmed in our study. The connecting linker does not play a direct role in the dephosphonylation process; however, it is important in distribution, elimination, and AChE reactivation rates (e.g., in the binding mechanism) [19]. …”
Section: Resultsmentioning
confidence: 99%
“…Tri or tetra-carbon linkers appear to be the most suitable for the reactivation process of soman, tabun, or cyclosarin-inhibited AChE [19] (Figure 2, n = 3,4). These derivatives of trimedoxime (compound 6 ) were prepared by Musilek et al and superior reactivation ability was confirmed for them over trimedoxime [20].…”
Section: Resultsmentioning
confidence: 99%
“…The obtained results in that investigation have been encouraging. 146 Nucleophilic reactivation of phosphylated AChE by an oxime occurs through the mechanism described in Figure 14. Usually, it is considered that the oxime reacts in the deprotonated form (oximate) in nucleophilic reactivation, as represented in Figure 14.…”
Section: Treatment and Antidotes For Nerve Agentsmentioning
confidence: 99%